Viral infections in septic shock (VISS-trial)-crosslinks between inflammation and immunosuppression - Brenner, Thorsten; Rosenhagen, Claudia; Hornig, Isabelle; Schmidt, Karsten; Mieth, Markus; Bruckner, Thomas; Martin, Eike; Schnitzler, Paul; Hofer, Stefan (Journal of surgical research, 2012)
Background: Recent investigations provided evidence that herpes simplex virus (HSV-1) and cytomegalovirus (CMV) are reactivated in critically ill individuals. However, at this time, it remains unclear whether these viral infections are of real pathogenetic relevance or represent innocent bystanders. Materials and Methods: In total, 60 patients with septic shock were enrolled. Blood samples and tracheal secretion were collected at the time of sepsis diagnosis (T0) as well as 7 d (T1), 14 d (T2), 21 d (T3), and 28 d (T4) later. The following virologic diagnostics were performed: (1) Viral load of herpes simplex virus type1 (HSV-1) and cytomegalovirus (CMV) in blood samples as well as tracheal secretion using polymerase chain reaction (PCR). (2) Detection of CMV-antigen (pp65) in blood samples using immunofluorescence microscopy. Furthermore plasma levels of interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α) were evaluated using ELISA-kits. Results: Thirty-one patients (51.7%) were found to be positive for HSV-1, whereas in 16 patients (26.7%) CMV could be identified. Patients with a positive PCR for HSV-1 and/or CMV showed a significantly prolonged length of hospital stay and absolute time of respirator-dependant ventilation. Furthermore, survival curves of patients with a high HSV-1-load (>10E8) in tracheal secretion in comparison with those with a lower HSV-1-load (<10E8) revealed a significantly impaired survival. Conclusions: Viral superinfections with HSV-1 or CMV can frequently be observed in patients with septic shock, especially in those with increased disease severity and a prolonged need for respirator-dependant ventilation. In patients with a viral superinfection morbidity is increased, whereas differences in mortality seem to be dosage-dependant.